Market surveillance of porcine DNA detection in commercial food products in Sibu, Sarawak - Yong, S.P. A.; Sajali, N.; Desa, M. N. M.; Koh, C. C.; Sani, M.; Wong, S. C.; Lani, M. N.; Wasoh, H.; Abubakar, S.
Porcine adulteration in food products is unacceptable to consumers who avoid pork consumption due to religious or health reasons; hence, detecting pork and its derivatives in food products is vital. The present work focused on assessing the DNA extraction efficiency of salt method as compared to the DNeasy mericon Food Kit to detect porcine DNA via quantitative PCR (qPCR), and comparing these qPCR findings with the food product labelling. The study selected food products which lacked JAKIM (Jabatan Kemajuan Islam Malaysia) certified halal logo, and those bearing foreign or counterfeit halal logos in Sibu, Sarawak. Twenty-four (n = 24) commercial food products, three (n = 3) pork-based products (positive control), and three (n = 3) JAKIM halal-certified products (negative control) were included. DNA was isolated and used as a template in a qPCR assay to target cytochrome b (cytb). Positive samples were sent for DNA sequencing. The experimental output was compared with the food ingredient and presence of a halal logo on product labelling. Out of 30 samples extracted using the DNeasy mericon Food Kit, DNA from all samples (100%) fell within the optimal DNA purity ratio which ranged from 1.7 to 2.0. The DNA extracted using this method was further used as a template in the qPCR. The qPCR assay demonstrated presence of porcine DNA in two food samples which lacked product labelling, with mean Ct values ± SD of 19.05 ± 0.72 and 28.07 ± 1.67 as compared to the positive control (mean Ct values ± SD of 13.44 ± 0.37 to 14.78 ± 1.10). Basic Local Alignment Search Tool (BLAST) analysis revealed a high percentage identity (94.74 - 100%) to Sus scrofa domesticus (pig) as compared to sequences in the National Centre for Biotechnology Information (NCBI) database. The present work demonstrated a significant halal status of various food items for Muslims and individuals with pork allergies in the studied area.